ANCIENT ROMAN ART - Edwards, Sean (UK Kruger Brentt Publishers, 2024)
This art history book will enlighten the significance of art in ancient Roman civilizations. It conveys the clear and balanced clarification of ideas and historical debates. This classic allows the booklover to imagine and appreciate the rich and diverse relics of Ancient past, transforming the method of discovering that past into a thrilling experience. This book will surely beneficial for the deep seekers of ancient Roman Artlovers.
Keywords: ART -- Pompeii -- Fora